2020
DOI: 10.1088/1755-1315/429/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Waveform re-tracking analyses with Fuzzy Logic on altimetry satellite data in Natuna Waters

Abstract: Waveform re-tracking analyses have been proven to increase the accuracy of sea surface height (SSH) estimation from satellite altimeters specifically in coastal areas. However, each re-tracking algorithm has its strengths and weaknesses so that no dominant algorithm can be applied to any water condition. The study purpose was to obtain the best SSH estimation from altimeter satellite data using waveform re-tracking analyses with fuzzy logic system. The fuzzy logic system was used to select the best SSH values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…They were found in near bay and small islands that had shallow waters (<200 m) and were close to the coastline (<17 km). Several studies in other regions reported similar findings, in which the peaky waveforms were found near to the coastline [8,25,29,46,47]. [8] also found that the highest percentage of peaky waveform was onshore, 5-6 km from the coastline.…”
Section: Waveform Classes In Halmahera Seasupporting
confidence: 59%
See 4 more Smart Citations
“…They were found in near bay and small islands that had shallow waters (<200 m) and were close to the coastline (<17 km). Several studies in other regions reported similar findings, in which the peaky waveforms were found near to the coastline [8,25,29,46,47]. [8] also found that the highest percentage of peaky waveform was onshore, 5-6 km from the coastline.…”
Section: Waveform Classes In Halmahera Seasupporting
confidence: 59%
“…Over the Indonesian seas, previous studies (e.g., [23,25,28,29]) reported the performance of several retrackers using the geoidal height data, which highlighting the precision of retracked SSHs. While the accuracy of the retrackers is also valuable, such studies are yet to be done, thus becoming the motivation of this study.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations